Expression and functional analysis of two PsbS genes in bamboo (Phyllostachys edulis). Issue 4 (23rd March 2018) - Lou, Yongfeng; Sun, Huayu; Wang, Sining; Xu, Hao; Li, Lichao; Zhao, Hansheng; Gao, Zhimin
Abstract : Higher plants have an array of photoprotection mechanisms alleviating the harmful effects of light. Non‐photochemical quenching (NPQ) is one of the photoprotective mechanisms, which dissipates the excess of light energy absorbed in the light‐harvesting complexes (LHCs) into thermal energy. The photosystem II subunit S (PsbS), a member of the LHC family thought to be present exclusively in higher plants, is supposed to activate NPQ through interactions with antenna proteins. However, the roles of PsbS in bamboo remain unclear. Here, two genes of bamboo ( Phyllostachys edulis ), PePsbS1 and PePsbS2, are investigated and functionally analyzed. PePsbS1 and PePsbS2 have a similar gene structure with three introns separated by two exons, which encode 269 and 268 amino acid residues, respectively. Tissue‐specific analysis showed that PePsbS1 and PePsbS2 are highly expressed in leaf blade. Besides, they are both upregulated in the leaf blade when plantlets are submitted to an increased and prolonged light intensity, suggesting that they are light‐induced. Western blot analysis indicated that the accumulation level of total PePsbSs is consistent with what obtained by quantitative real‐time polymerase chain reaction for PePsbS1 and PePsbS2 . Transgenic Arabidopsis plants overexpressing PePsbS1 and PePsbS2 both displayed an enhanced photoprotection. Moreover, the expression of PePsbS1 and PePsbS2 could both rescue the NPQ of Arabidopsis npq4 mutant, indicating that the PsbS s are functionally conserved between monocots and dicots. These results indicated that both PePsbS1 and PePsbS2 could circumvent photoinhibition and enhance photoprotection, which are key factors for bamboo's adaptation to different light environment.